Epigenetic Environmental Memories in Plants: Establishment, Maintenance, and Reprogramming. Issue 11 (November 2018) - He, Yuehui; Li, Zicong
Abstract : Plants are immobile and must respond to or endure fluctuating surroundings and diverse environmental challenges. Environmental inputs often induce chromatin modifications at various responsive genes and consequent changes in their expression. Environment-induced chromatin marks at certain loci are transmittable through cell divisions after relief from the original external signals, leading to acquired 'memorization' of environmental experiences in plants, namely epigenetic environmental memories, which enable plants to adapt to environmental changes or to perform better when events recur. Here, we review recent progress in epigenetic or chromatin-mediated environmental memories in plants, including defense priming, stress memories, and 'epigenetic memory of winter cold' or vernalization. Various advances in epigenetic mechanisms underlying plant–environment interactions highlight that plant environmental epigenetics is emerging as an important area in plant biology. Highlights: Plants can 'memorize' certain past environmental experiences, and environment-induced chromatin modifications at responsive loci underlie environmental memory. Stress memories allow plants respond more quickly and vigorously to recurring stresses to increase stress tolerance or avoidance ability. Through 'epigenetic memory of winter cold', vernalization-responsive annuals or biennials adapt to winter cold and flower under favorable conditions in spring; the cycle of cold memorization–memory erasure enables each generation to adapt to seasonal temperature drop in winter. Each generation faces a different combination of environmental challenges, and the loss or erasure of most environmental memories enables a fresh start for the next generation and ensures 'normal' growth and development of offspring. Plant environmental epigenetics is emerging as an important area in plant biology.